Are Interests of Business Actors and Consumers Balanced in The Indonesian Competition Law? - Moch. Zairul Alam; Kukuh Tejomurti (Faculty of Law, Maranatha Christian University, 2022)
This paper aims to provide a critical analysis to the relations between economic efficiency and justice as the objectives of business competition law in Indonesia within the framework of legal philosophy. Philosophical aspects explores view on equal opportunities for every citizen in their business behavior, relation between the principles of justice and efficiency considering that in the Law 5 of 1999 there is no any word “justice” mentioned. Several related schools of legal philosophy will use to analyse the problems, such as, Utilitarianism in dissecting the phrase